A Review on Turkey’s Renewable Energy Potential and its Usage Problems - Tutar, Hasan; Atas, Mehmet (International Journal of Energy Economics and Policy, 2022)
The need for energy resources in the world continues to increase day by day. Energy demand will increase in the coming years in parallel with population growth, industrialization and technological developments, especially in developing countries. The fact that fossil energy sources cause environmental problems, their reserves will be depleted shortly, dependence on source countries causes various political and economic problems, and price instability increases the interest in renewable energy sources. Especially in developed countries, renewable energy sources such as hydraulic, wind, geothermal, solar, biomass, wave, hydrogen etc. Energy sources are used in various ways, especially electricity production. As a developing country, Turkey's need for energy resources increases day by day in parallel with its increasing population and growing economy. Turkey, which is approximately 75% foreign-dependent in terms of its current energy structure, seems to be a necessity rather than a choice to reduce this dependency on renewable energy sources. In this study, Turkey's current renewable energy potential has been revealed, and various suggestions have been made by analyzing the renewable energy potential.